MANAJEMEN KEARSIPAN DALAM MENINGKATKAN PELAYANAN ADMINISTRASI DI KANTOR BADAN PERTANAHAN NASIONAL (BPN) KABUPATEN GOWA - Sasmint, Yuyun Andira; Usman, Jaelan; Wahid, Nur (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to determine archive management in improving administrative services at the Gowa Regency National Land Agency (BPN) Office. This research uses qualitative methods, with a qualitative descriptive research type. Data sources consist of primary data and secondary data. Data analysis techniques involve data reduction, data presentation, and drawing conclusions. The results of the research show that (a) archival recording at the Gowa Regency Land Office is classified as good, (b) control and distribution at the Gowa Regency Land Office is running optimally, (c) archival storage at the Gowa Regency Land Office is by using a subject system, (d) archives at the Gowa Regency Land Office are maintained quite well, (e) supervision of archives at the Gowa Regency Land Office has also carried out quite good supervision in the field of archives, (f) transfer and destruction at the Gowa Regency Land Office is ongoing maximally